Risk of Fractures and Falls during and after 5-α Reductase Inhibitor Use: A Nationwide Cohort Study - Robinson, David; Garmo, Hans; Stattin, Pär; Michaëlsson, Karl (PLOS ONE, 2015)
Background Lower urinary tract symptoms are common among older men and 5-α reductase inhibitors (5-ARI) are a group of drugs recommended in treating these symptoms. The effect on prostate volume is mediated by a reduction in dihydrotestosterone; however, this reduction is counterbalanced by a 25% rise in serum testosterone levels. Therefore, 5-ARI use might have systemic effects and differentially affect bone mineral density, muscular mass and strength, as well as falls, all of which are major determinants of fractures in older men. Methods We conducted a nationwide cohort study of all Swedish men who used 5-ARI by comparing their risk of hip fracture, any type of fracture and of falls with matched control men randomly selected from the population and unexposed to 5-ARI. Results During 1 417 673 person-years of follow-up, 10 418 men had a hip fracture, 19 570 any type of fracture and 46 755 a fall requiring hospital care. Compared with unexposed men, current users of 5-ARI had an adjusted hazard ratio (HR) of 0.96 (95% CI 0.91–1.02) for hip fracture, an HR of 0.94 (95% CI 0.90–0.98) for all fracture and an HR of 0.99 (95% CI 0.96–1.02) for falls. Former users had an increased risk of hip fractures (HR 1.10, 95% CI 1.01–1.19). Conclusion 5-ARI is safe from a bone health perspective with an unaltered risk of fractures and falls during periods of use. After discontinuation of 5-ARI, there is a modest increase in the rate of fractures and falls.